Historical evidence for larger government spending multipliers in uncertain times than in slumps - Pascal Goemans (Economic Inquiry, 2022)
We investigate whether US government spending multipliers are higher during periods of heightened uncertainty or economic slumps as opposed to normal times. Using quarterly data from 1890 onward and local projections, we estimate a cumulative 1-year multiplier of 2 during uncertain periods. In contrast, the multiplier is about 1 in times of high unemployment and about 0.4–0.8 during normal times. While we find positive employment effects in slumps as well as in uncertain times, two transmission channels can explain the higher multipliers in the latter: greater price flexibility leading to short-term inflation (lowering the real interest rate) and diminishing risk premiums.
Keywords: 330; fiscal policy; government spending multiplier; historical data; local projections; slump; uncertainty